2010
DOI: 10.4103/0976-3147.63106
|View full text |Cite
|
Sign up to set email alerts
|

Communication between radial nerve and medial cutaneous nerve of forearm

Abstract: Radial nerve is usually a branch of the posterior cord of the brachial plexus. It innervates triceps, anconeous, brachialis, brachioradialis, extensor carpi radialis longus muscles and gives the posterior cutaneous nerve of the arm, lower lateral cutaneous nerve of arm, posterior cutaneous nerve of forearm; without exhibiting any communication with the medial cutaneous nerve of forearm or any other nerve. We report communication between the radial nerve and medial cutaneous nerve of forearm on the left side in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In 2007, Huanmanop et al [ 14 ] concluded that connections between the SBRN and the LABCN are common but replacements are rare and these variations are important to know in cases of peripheral nerve injuries. Several researchers studied branching patterns of the musculocutaneous nerve and radial nerves [ 15 16 ]. Tryfonidis et al [ 17 ] reported the variation in the course of the SBRN.…”
Section: Discussionmentioning
confidence: 99%
“…In 2007, Huanmanop et al [ 14 ] concluded that connections between the SBRN and the LABCN are common but replacements are rare and these variations are important to know in cases of peripheral nerve injuries. Several researchers studied branching patterns of the musculocutaneous nerve and radial nerves [ 15 16 ]. Tryfonidis et al [ 17 ] reported the variation in the course of the SBRN.…”
Section: Discussionmentioning
confidence: 99%
“…Very rarely might a communication be observed between ulnar nerve and medial cutaneous nerve of forearm. Medial cutaneous nerve of forearm is found to communicate with medial cutaneous nerve of arm [ 7 ] and radial nerve [ 16 ]. Das and Paul reported a case wherein the ulnar nerve was accompanied by the medial cutaneous nerve of forearm within a common fascial sheath [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“… Pattern 1: Both nerves are completely fused, and the MN consists of three roots (this anastomosis occurred in about 19.2%) [29,30],  Pattern 2: There is a single interconnecting branch (the most common variation, prevalence 72.6%),  Pattern 3: There are two supplementary branches (about 6.8% in cadaveric studies) [9,25,26]. Marathe et al [54] ascribed this variation to the stage in embryo development when somites migrate and form buds (anlage of the limbs). At approximately the fifth week of intrauterine life, the forelimb muscles develop from the mesenchyme of the paraxial mesoderm.…”
Section: Figure B1mentioning
confidence: 99%
“…Tropic substances such as brain-derived neurotropic growth factor, neutrin-1, neutrin-2, and c-kit ligand allow the appropriate growth cones to be attracted or selectively maintain those that follow the correct path. Variations in nerve distribution could result from altered signaling between mesenchymal cells and neuronal growth cones, or circulating factors, during fission of the brachial plexus [54].…”
Section: Figure B1mentioning
confidence: 99%
See 1 more Smart Citation